2017
DOI: 10.1111/1462-2920.13995
|View full text |Cite
|
Sign up to set email alerts
|

Obligate sugar oxidation in Mesotoga spp., phylum Thermotogae, in the presence of either elemental sulfur or hydrogenotrophic sulfate‐reducers as electron acceptor

Abstract: Mesotoga prima strain PhosAc3 is a mesophilic representative of the phylum Thermotogae comprising only fermentative bacteria so far. We show that while unable to ferment glucose, this bacterium is able to couple its oxidation to reduction of elemental sulfur. We demonstrate furthermore that M. prima strain PhosAc3 as well as M. prima strain MesG1 and Mesotoga infera are able to grow in syntrophic association with sulfate-reducing bacteria (SRB) acting as hydrogen scavengers through interspecies hydrogen transf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 34 publications
(11 citation statements)
references
References 47 publications
0
11
0
Order By: Relevance
“…Instead Fadhlaoui et al . () showed that Mesotoga spp. prefer to grow in syntrophy with hydrogenotrophic sulfate‐reducing bacteria.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…Instead Fadhlaoui et al . () showed that Mesotoga spp. prefer to grow in syntrophy with hydrogenotrophic sulfate‐reducing bacteria.…”
Section: Resultsmentioning
confidence: 99%
“…The Mesotoga genomes and transcriptome also elucidated the genetic background for their distinct energy metabolism compared with thermophilic Thermotogae bacteria, that is, the strict need for sulfur or thiosulfate and no or little H 2 production, but rather H 2 S production unless in co‐culture with a sulfate reducer (Fadhlaoui et al ., ). Fadhlaoui et al .…”
Section: Discussionmentioning
confidence: 97%
See 3 more Smart Citations